Taxonomic review of the genus Meleonoma Meyrick (Lepidoptera: Autostichidae), with a checklist of all the described species - Wang, Shuxia; Zhu, Xiaoju; Zhao, Baixue; Yang, Xiaofei (Zootaxa, 2020)
Meleonoma Meyrick, 1914 is treated as a genus of the family Autostichidae based on the recent study. Fifty species are transferred from the genus Cryptolechia to Meleonoma, and eight Meleonoma species groups are proposed for the taxonomic convenience based on both molecular data and morphological study. Eight species groups include: the malacobyrsa group, the segregnatha group, the annulignatha group, the fasciptera group, the jigongshanica group, the dentivalvata group, the facialis group, and the acutiuscula group. Diagnostic characters and representative illustrations of each species group are provided. A discussion on the proposed species groups is given, and a checklist of all the 88 described Meleonoma species is provided.